Four eyes principle reduces re-operation rate in converting phase from open to laparoscopic pyloromyotomy - Meyer, J.; Spacil, Karel; Stehr, Maximilian; Schäfer, Frank-Mattias (Journal of Pediatric Surgery, 2025)
Introduction: Laparoscopic pyloromyotomy is now considered standard procedure in patients with infantile pyloric stenosis with many pediatric surgery departments converting from open to laparoscopic procedures. The four eyes principle describes an internal mechanism to improve safety both in medical and non-medical fields. In this conversion phase we hypothesized that introduction of the four eyes principle in laparoscopic pyloromyotomy may lead to less complications. Material and methods: We retrospectively analyzed patients with infantile pyloric stenosis operated on in our department in the last ten years. Patients were grouped into open surgery group (OS), laparoscopic surgery group (LS) and laparoscopic surgery with the four eyes principle group (FELS) and compared all three groups regarding the main complications classified as incomplete myotomy or mucosal perforation as well as all re-operations due to main complications. Results: Overall, 103 patients (84 male and 19 female) were included in the analysis (24 LS, 49 OS, 26 FELS). Mean operating time was 30.5 min. (LS), 34.5 min (FELS) and 41.0 min. (OS) respectively. Postoperative in-house stay was 4.8 days in LS, 4.5 days in OS and 4.0 days in FELS. Patients in FELS had significantly fewer reoperations due to main complications compared to patients in LS (p 0.0336). OS and FELS did not show significant differences in re-operation rates or main complications. Conclusions: Application of the four eyes principle helps to reduce rate of re-operations in laparoscopic pyloromyotomy in converting phase from open to laparoscopic procedures. Especially in view of presumably decreasing incidence in infantile pyloric stenosis, the four eyes principle seems to be a valuable tool to decrease the learning curve.
CRIS-Team Scopus Importer:2025-09-26
Keywords: Four eyes principle; Laparoscopic pyloromyotomy; Pyloric stenosis